The Attitudes Towards Social Class Inequality Conflict in the Movie “Kabhi Khushi Kabhi Gham” by Karan Johar - Nofansyah; Waladdin Panggabean (Faculty of Letters Universitas Balikpapan, 2023)
This research explores forms of attitudes and social class inequality conflict in the movie “Kabhi Khushi Kabhi Gham”. There are two objectives in this research; 1) To find and describe forms of attitudes in the movie Kabhi Khushi Kabhi Gham By Karan Johar. 2) To find and describe attitudes affect social class inequality conflict. The theory used in this research is Marxism using Karl Marx theory of conflict. The methodology employed is qualitative research in which the researcher tried to present the issues descriptively. As for the data, they were collected from the scenes and english dialogue script in the movie. The movie was taken out as the primary data. The method used by the writer in collecting data is library research. When data is collected and researched. Finally, the data was analyzed descriptively based on theory. After going through the analysis, the researcher finds the forms of attitudes and attitudes affect social inequality conflict were found in findings and discussion. The forms of attitudes that found based in the movie are happen in society, and the attitude affect the social inequality conflict based in the movie that have been found are economy status, social and social class inequality conflict.